A Carbon Nanotube Optical Sensor Reports Nuclear Entry via a Non-Canonical Pathway - Budhathoki-Uprety, Januka (ACS Nano, 2017)
Single-walled carbon nanotubes are of interest in biomedicine for imaging and molecular sensing applications, and as shuttles for various cargos such as chemotherapeutic drugs, peptides, proteins, and oligonucleotides. Carbon nanotube surface chemistry can be modulated for subcellular targeting while preserving photoluminescence for label-free visualization in complex biological environments, making them attractive materials for such studies. The cell nucleus is a potential target for many pathologies including cancer and infectious diseases. Understanding mechanisms of nanomaterial delivery to the nucleus may facilitate diagnostics, drug development, and gene editing tools. Currently, there are no systematic studies to understand how these nanomaterials gain access to the nucleus. Herein, we developed carbon nanotube-based hybrid material which elucidated a distinct mechanism of nuclear translocation of a nanomaterial in cultured cells. We developed a nuclear-targeted nanotube via cloaking photoluminescent single-walled carbon nanotubes in a guanidinium-functionalized helical polycarbodiimide. We found that the nuclear entry of the nanotubes was mediated by the import receptor importin β without the aid of importin α and not by the more common importin α/β pathway. Additionally, the nanotube photoluminescence exhibited distinct red-shifting upon entry to the nucleus, potentially functioning as a reporter of the importin β-mediated nuclear transport process. This work delineates a non-canonical mechanism for nanomaterial delivery to the nucleus and provides a reporter for the study of nucleus-related pathologies.